Enhancing the sustainability of waqf: a thematic review exploration across financial, social, and environmental, governance dimensions - Baharin, NorBahriah; Siraj, Siti Alawiah; Osman@Hussin, Ahmad Zamri; Mohd Ariffin, Noraini (Human Resource Management Academic Research Society (HRMARS), 2025)
Waqf, a cornerstone of Islamic philanthropy, has historically contributed to socio-economic and environmental sustainability. Despite its significant potential, waqf institutions face limited governance frameworks, outdated practices, and insufficient integration with contemporary financial and technological systems. These gaps hinder its alignment with modern sustainability objectives, particularly in addressing economic, social, environmental, and governance-related issues. This study explores and enhances waqf’s sustainability through a thematic review encompassing five key areas: financial sustainability and economic development, community empowerment and social welfare, innovative waqf models and practices, environmental sustainability, and governance and legal frameworks. This study employed a structured thematic analysis and synthesised findings from recent literature published between 2018 and 2024. The results reveal that waqf’s potential can be maximised through innovative financial models, community-driven initiatives, green strategies, and robust governance mechanisms. Contributions include cash waqf integration with microfinance, productive waqf initiatives in education and agriculture, and adopting governance frameworks that align with sustainable development goals. These findings demonstrate waqf's adaptability to modern challenges, showcasing its role in promoting financial inclusion, community resilience, and ecological conservation. Future research should focus on digitalising waqf management, exploring interdisciplinary approaches, and scaling innovative models across diverse socio-economic landscapes. The study contributes to academia by filling gaps in waqf-related sustainability research. It offers practitioners actionable strategies for optimising waqf’s impact, positioning it as a vital tool for achieving comprehensive sustainability in a rapidly evolving global context.